2018
DOI: 10.1021/acs.est.8b02403
|View full text |Cite
|
Sign up to set email alerts
|

Enhancement of H2O2 Decomposition by the Co-catalytic Effect of WS2 on the Fenton Reaction for the Synchronous Reduction of Cr(VI) and Remediation of Phenol

Abstract: The greatest problem in the Fe(II)/HO Fenton reaction is the low production of ·OH owing to the inefficient Fe(III)/Fe(II) cycle and the low decomposition efficiency of HO (<30%). Herein, we report a new discovery regarding the significant co-catalytic effect of WS on the decomposition of HO in a photoassisted Fe(II)/HO Fenton system. With the help of WS co-catalytic effect, the HO decomposition efficiency can be increased from 22.9% to 60.1%, such that minimal concentrations of HO (0.4 mmol/L) and Fe (0.14 mm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
94
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 351 publications
(95 citation statements)
references
References 89 publications
1
94
0
Order By: Relevance
“…k (COH/l-AA) = 1.1 10 10 m À1 s À1 , k (COH/ HA) = 0.5-9.5 10 9 m À1 s À1 ), giving rise to al ow mineralization efficiency of the target contaminants. [9b,10] Lately,m etal sulfides such as WS 2 and MoS 2 with reductive metallic sites were used to promote Fe II regeneration and enhance Fenton oxidation, however, the coupled systems required light irradiation and might cause secondary contamination due to the leached metal ions and generation of toxic H 2 S. [11] Boron is am etalloid element and locates between the nonmetallic carbon and metallic beryllium in the periodic table.Electron-deficient boron atoms bond with each other to form icosahedral B 12 monomers via electron-sharing B À B bonds,c onsequently building the bulk architecture via twocenter-and three-center-two-electron shared BÀBbonds into manifold interlinked polyhedron. [12] It has been reported that diboron compounds with BÀBb onds can serve as electron donors and contribute reductive sites to the surface of TiO 2 , ZnO,SnO 2 ,Nb 2 O 5 ,and In 2 O 3 via strong interfacial coupling, which affords 1000 times greater visible light response to enhance the performance of perovskite solar cells.…”
Section: Introductionmentioning
confidence: 99%
“…k (COH/l-AA) = 1.1 10 10 m À1 s À1 , k (COH/ HA) = 0.5-9.5 10 9 m À1 s À1 ), giving rise to al ow mineralization efficiency of the target contaminants. [9b,10] Lately,m etal sulfides such as WS 2 and MoS 2 with reductive metallic sites were used to promote Fe II regeneration and enhance Fenton oxidation, however, the coupled systems required light irradiation and might cause secondary contamination due to the leached metal ions and generation of toxic H 2 S. [11] Boron is am etalloid element and locates between the nonmetallic carbon and metallic beryllium in the periodic table.Electron-deficient boron atoms bond with each other to form icosahedral B 12 monomers via electron-sharing B À B bonds,c onsequently building the bulk architecture via twocenter-and three-center-two-electron shared BÀBbonds into manifold interlinked polyhedron. [12] It has been reported that diboron compounds with BÀBb onds can serve as electron donors and contribute reductive sites to the surface of TiO 2 , ZnO,SnO 2 ,Nb 2 O 5 ,and In 2 O 3 via strong interfacial coupling, which affords 1000 times greater visible light response to enhance the performance of perovskite solar cells.…”
Section: Introductionmentioning
confidence: 99%
“…The dissimilar enhancement is attributed to the specific ROS generated in the three systems [Eq. (1), (10), (11)], [4,14] because DEP is more readily to react with COH (3.7 10 9 m À1 s À1 )c ompared to SO 4 C À (6.3 10 7 m À1 s À1 ). [15] Fe II þ HSO 5…”
Section: Introductionmentioning
confidence: 99%
“…Various types of biological and physical methods have been utilized to remove organic compounds from industrial wastewater. Biological treatment is a cost-effective technology of removing organic dye from wastewater but suffers from some drawbacks, such as easy inactivation, owing to the toxic biological effects from organic chemicals [3]. Ion exchange or adsorption is also a common and effective means of removing organic pollutions.…”
Section: Introductionmentioning
confidence: 99%
“…Ion exchange or adsorption is also a common and effective means of removing organic pollutions. However, post-treatments are usually required to regenerate the resins/adsorbents and prevent secondary contamination [3]. Thus, AOPs, Fenton and Fenton-like reactions have been widely studied due to their high efficiency in generating hydroxyl radicals for decontamination of recalcitrant organic pollutants.…”
Section: Introductionmentioning
confidence: 99%